I segnali discorsivi interazionali nel parlato di bambini plurilingui. : Aspetti acquisizionali e fenomeni di contatto tra ladino, tedesco e italiano (Linguistik Online, 2025)
The aim of this paper is to investigate the use of interactional pragmatic markers in a multilingual corpus of child language in the Ladin valleys in South Tyrol (Italy). It has been argued that in contact-induced contexts speakers tend to prefer the set of elements of the pragmatically dominant language, in order to reduce the cognitive pressure they are exposed to, in particular in a minority language (cf. Matras 2000). Yet, very little is known about the use of pragmatic markers in child language, even though the pragmatic competence, i. e. the appropriate use of language as well as the proper realization of speech acts in a particular situational context, is one of the key competences children need to acquire during the language acquisition process. The present study was carried out within the sociolinguistic framework of the Ladin valleys, which is characterized by a varied multilingualism on the institutional level and in family contexts. The corpus contains approximately eight hours of spoken data from eight children aged three to six across the three official languages Ladin, German and Italian. This work aims at analysing the micro-functions of interactional pragmatic markers and at investigating how the use of these elements is linked to the linguistic and cognitive development of preschool children. It also contributes to the study of contact-induced phenomena that emerge in a multilingual context.